Perbandingan Komitmen Perkawinan antara Laki-Laki dan Perempuan yang sudah Menikah di Bandung - Cindy Maria; Stephanie Andamari (Humanitas (Jurnal Psikologi), 2019)
Abstract Commitment to a marriage is one of the most important factors that lead a family to belong last. This study examined the marriage commitment levels between married men and women in Bandung. The researcher uses the Investment Model measurement tool from Rusbult's theory to capture commitment level, level of satisfaction, alternative quality and investment size. This measurement has a range of validity 0.46-0.84 and reliability 0.83-0.92. The sampling technique used was accidental sampling, with 600 respondents consisting of 300 men and 300 women who have been married for at least five years. Data analyses were carried out with Mann-Whitney’s comparison tests. The results showed that there was no difference in commitment between men and women who had been married for more than 5 years. There was not any contribution founded between demographic factors and marriage commitment levels. Keywords: marriage commitment, level of satisfaction, alternative quality, investment size